Analisis Faktor-Faktor Yang Mempengaruhi Penerimaan Pajak Reklame Kota Banjarmasin - Safarina Mahmudah; Lina Suherty (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2022)
This research is processed with the aim of seeing and proving the strength of the relationship between inflation, number of companies, and company services on advertisement tax revenues in Banjarmasin City. The scope of this research itself is the advertisement tax in the city of Banjarmasin which uses multiple linear regression analysis with quantitative descriptive data collection techniques taken from secondary data to facilitate researchers in researching in the midst of this pandemic situation, and sourced from the literature (library) and data from official data requested at the official agency. The results of this study are that there is a joint influence between the amount of inflation, the number of companies, and company services on advertisement tax revenues in Banjarmasin City. While partially there are two variables that have a positive and significant influence, namely the inflation variable and the number of companies in Banjarmasin City. In line with the test results, the most dominant variable influencing is the number of companies.